Targeting Cytokine Signals to Enhance γδT Cell-Based Cancer Immunotherapy - Song, Yuan; Liu, Yonghao; Teo, Huey Yee; Liu, Haiyan (Frontiers in Immunology, 2022)
γδT cells represent a small percentage of T cells in circulation but are found in large numbers in certain organs. They are considered to be innate immune cells that can exert cytotoxic functions on target cells without MHC restriction. Moreover, γδT cells contribute to adaptive immune response via regulating other immune cells. Under the influence of cytokines, γδT cells can be polarized to different subsets in the tumor microenvironment. In this review, we aimed to summarize the current understanding of antigen recognition by γδT cells and the immune regulation mediated by γδT cells in the tumor microenvironment. More importantly, we depicted the polarization and plasticity of γδT cells in the presence of different cytokines and their combinations, which provided the basis for γδT cell-based cancer immunotherapy targeting cytokine signals.